2016
DOI: 10.1016/j.dnarep.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Nonhomologous end joining of complex DNA double-strand breaks with proximal thymine glycol and interplay with base excision repair

Abstract: DNA double-strand breaks induced by ionizing radiation are often accompanied by ancillary oxidative base damage that may prevent or delay their repair. In order to better define the features that make some DSBs repair-resistant, XLF-dependent nonhomologous end joining of blunt-ended DSB substrates having the oxidatively modified nonplanar base thymine glycol at the first (Tg1), second (Tg2), third (Tg3) or fifth (Tg5) positions from one 3′ terminus, was examined in human whole-cell extracts. Tg at the third po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…On the other hand, it seems unlikely that the residual 3′-dephosphorylation is the result of general broad-specificity phosphatases, since it is regulated by DNA-PK. Furthermore, it appears to act specifically on 3′- and not 5′-phosphates, as indicated by the retention of 5′- 32 P label on DSB substrates even after incubation in whole-cell extracts for many hours [14,47]. Rather, overall the data suggest an enzyme that acts specifically in NHEJ, in a manner similar to PNKP but less efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it seems unlikely that the residual 3′-dephosphorylation is the result of general broad-specificity phosphatases, since it is regulated by DNA-PK. Furthermore, it appears to act specifically on 3′- and not 5′-phosphates, as indicated by the retention of 5′- 32 P label on DSB substrates even after incubation in whole-cell extracts for many hours [14,47]. Rather, overall the data suggest an enzyme that acts specifically in NHEJ, in a manner similar to PNKP but less efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…Using blunt-ended DSB substrates harboring the oxidatively modified nonplanar base thymine glycol (Tg) at the first, second, third or fifth positions from one 3′ terminus (Tg1, Tg2, Tg3 and Tg5 respectively), NHEJ of damaged DSB ends was examined in human whole-cell extracts [38]. In XLF-deficient extracts, end joining of all substrates, including unmodified blunt ends, was completely dependent on addition of recombinant XLF.…”
Section: Xlf Structurementioning
confidence: 99%
“…5, however, POLB À/À cells were slightly but reproducibly more resistant to highdose x-ray (>4 Gy) than WT cells. Consistent with this view, Almohaini et al [35] have reported that BER can interfere with NHEJ when thymine glycol is formed at the fifth base from the 3' terminus of one DNA end. As x-ray can induce DSB-clustered lesions, which associate DSBs and several base damage and abasic sites in close vicinity [34], POLb-dependent BER may prevent efficient repair of such lesions in the presence of NHEJ.…”
Section: Polb Is Important For Cell Survival After Irradiation When Nmentioning
confidence: 76%
“…As x-ray can induce DSB-clustered lesions, which associate DSBs and several base damage and abasic sites in close vicinity [34], POLb-dependent BER may prevent efficient repair of such lesions in the presence of NHEJ. Consistent with this view, Almohaini et al [35] have reported that BER can interfere with NHEJ when thymine glycol is formed at the fifth base from the 3' terminus of one DNA end. Live cell imaging also revealed that BER factors (such as PARP-1 and XRCC1) rapidly accumulate at laser-induced DNA damage sites, in a manner similar to NHEJ factors [36].…”
Section: Polb Is Important For Cell Survival After Irradiation When Nmentioning
confidence: 76%